A Comprehensive Investigation on the Determinant Factors of Cultural Competency on Native Physician-Medical Tourists Interactions: A Case of South Korea - Rokni, Ladan (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2017)
Medical tourism as a service sector has brought authorities to a position in which they are required to revise their innovative competitive advantages. Non-clinical services are likely to be efficient to respond the demands in medical tourism. Doctor-patient interactions, is one of the most efficient strategy to deliver non-clinical services. Level of cultural competency can address the need of culturally appropriate service. Hence, it is essential to examine the determinants of cultural competency in medical tourism. In this study, an exploratory approach through a mix of qualitative and quantitative methodologies was adopted. The research was conducted in three main phases. The common point among the participants in 3 phases was to be active in the medical tourism. Results were reported based on the aims of study, the barriers of medical tourism development in Korea were reported, a framework of cultural competence delivery was developed. It was followed by expert’s confirmation and finally the construct of the framework was tested. Delivering cultural competence in medical tourism would not occur appropriately unless a systematic combination of personal characteristics, external supports, and skillful abilities are established. Therefore, it is essential for authorities to focus on the workforce improvement in medical tourism. Besides, those individuals working in this domain are required to provide personal attempt, commitment, desire and abilities to adopt the best of their knowledge.

ÖZ: Bir hizmet sektörü olarak tıp turizmi yetkilileri yenilikçi rekabet faydalarını gözden geçirmeye itmiştir. Klinik dışı hizmetlerin tıp turizmindeki ihtiyaçlara yanıt verirken etkin bir rol üstlendiği görülmektedir. Doktor hasta ilişkileri, klinik dışı hizmet vermek için en yüksek etkili stratejilerden biridir. Kültürel yetkinlik seviyesi, kültürel uyum servisine duyulan ihtiyaca dikkat çekmektedir. Bu yüzden, kültürel yetkinlik seviyesinin etmenkerini sınamak gerekir. Bu çalışmada, nitel ve nicel yöntemlerden oluşan keşifsel araştırma teknikleri kullanılmıştır. Araştırma üç ana evre üzerinden yürütülmüştür. Katılımcıların tıp turiziminde aktif rol almaları üç evrede de ortak noktadır. Sonuçlar çalışmanın hedeflerine göre, Kore’de tıp turizminin karşılaştığı engellere göre raporlanmıştır, Kültürel yetkinlik seviyesinde bir çerçeve geliştirilmiştir. Bunu, uzman tastiği takip etmiş, son olarak da, çizilen çerçeve test edilmiştir. Araştırma sonuçlarına göre doktorların özellikleri, dış destek ve mesleki becerilerin arasında başarılı bir kombinasyonu olmadan doğru bir kültürel yeterlilik ve klinik dışı hizmetler vermek mümkün olmayacaktır. Bu nedenle, yetkililerin Tıbbi Turizm'deki insan kaynaklarına odaklanması, örgütsel ve eğitimsel destek sağlayarak sektörün gelişmesine yardımcı olması gerekmektedir. Ayrıca, bu alandaki kişiler, yeni koşullara dayalı bilgi ve becerilerini geliştirmeyi kabul etmeli ve yerine getirebilmelidir.
Doctor of Philosophy in Tourism Management. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Tourism, 2017. Co-Supervisor: Prof. Dr. Sam Hun Park and Supervisor: Prof. Dr. Turgay Avcı.
Keywords: Banking and Finance; Medical Tourism--South Korea; Medical tourism; Cultural competence; Cross-cultural interaction; Doctor-patient interaction; Korea